Absent Pulmonary Valve, Tricuspid Atresia, and Congenital Heart Block. (January 2015) - Juaneda, Ignacio; Rychik, Jack; Fuller, Stephanie; Weinberg, Paul M.; Rome, Jonathan J.; Mahle, William T.; Gaynor, J. William
We describe management of a patient with a prenatal diagnosis of absent pulmonary valve, tricuspid atresia, ventricular septal defect, and congenital heart block. Initial treatment consisted of temporary pacemaker implantation, and subsequent palliation included a central shunt during the neonatal period and placement of a permanent pacemaker. At seven months of age, a bidirectional Glenn anastomosis was performed. Cardiac catheterization revealed high cavopulmonary pressures and ventricular dysfunction precluding Fontan completion. Heart transplantation was performed at 3.75 years of age. The patient is alive and well 26 months posttransplantation.